TINDAK PIDANA PENCUCIAN UANG DALAM PERSPEKTIF FILSAFAT HUKUM - Diana Darmayanti Putong; Natalia Artha Malau (Honeste Vivere, 2026)
Money laundrying is a badness yielding properties possession in numbera real big or properties possession genesis is result of badness, the hidden or disguised variously. This badness longer increasingly increases, so that must be fought against that insentity crime yielding or entangles properties possession that is the numbers big earned diminalisation so that economics stability of state and security and safety of state can awake. Method applied is bibliography study, result of is money laundrying is badness of transnasional because getting through state region boundarys, the eradication cannot be done self, but that be effective must be done cooperation International through multilateral or bilateral forum and must fulfill standard International.